Frameless stereotactic radiosurgery of a solitary liver metastasis using active breathing control and stereotactic ultrasound = Rahmenlose stereotaktische Radiochirurgie einer solitären Lebermetastase durch aktive Atmungskontrolle und stereotaktischen Ultraschall - Boda-Heggemann, Judit; Walter, Cornelia; Mai, Sabine; Dobler, Barbara; Dinter, Dietmar; Wenz, Frederik; Lohr, Frank (Strahlentherapie und Onkologie, 2006)
Background and Purpose: Radiosurgery of liver metastases is effective but a technical challenge due to respiration-induced movement. The authors report on the initial experience of the combination of active breathing control (ABC((R))) with stereotactic ultrasound (B-mode acquisition and targeting [BAT((R))]) for frameless radiosurgery. Patient and Methods: A patient with a solitary, inoperable Liver metastasis from cholangiocellular carcinoma is presented (Figure 4). ABC((R)) (Figure 3) was used for tumor/liver immobilization. Tumor/liver position was controlled and corrected using ultrasound (BAT((R)); Figure 1). The tumor was irradiated with a single dose of 24 Gy. Results: Using ABC((R)), the motion of the tumor was significantly reduced and the overall positioning error was < 5 mm (Figure 2). BAT((R)), allowed a rapid Localization of the Lesion during breath hold which could be performed without difficulties for 20 s. Overall treatment time was acceptable (30 min). Conclusion: Frameless stereotactic radiotherapy with the combination of ABC((R)) and BATs allows the delivery of high single doses to targets accessible to ultrasound with high precision comparable to a frame-based approach.